2021
DOI: 10.1021/acsnano.1c01256
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Self-Powered High-Performance Integrated Nanostructured-Gas-Sensor Network for Future Smart Homes

Abstract: The accelerated evolution of communication platforms including Internet of Things (IoT) and the fifth generation (5G) wireless communication network makes it possible to build intelligent gas sensor networks for real-time monitoring chemical safety and personal health. However, this application scenario requires a challenging combination of characteristics of gas sensors including small formfactor, low cost, ultralow power consumption, superior sensitivity, and high intelligence. Herein, self-powered integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 44 publications
(59 reference statements)
2
68
0
Order By: Relevance
“…A 1g Raman peak observed from the exfoliated MoS 2 is blue-shifted from 403 to 401 cm −1 , while E 2g 1 Raman peak is red-shifted from 377 to 379 cm −1 . The results agree well with the literature that reported the E 2g 1 and A 1g modes are moving toward each other with decreasing layer thickness. 37 Moreover, the Raman peak difference of the exfoliated MoS 2 also approximate the number of MoS 2 layers, and a measured value of 22 cm −1 for the exfoliated MoS 2 dispersion corresponds to double-layer MoS 2 .…”
Section: Characterization Of Mossupporting
confidence: 92%
See 1 more Smart Citation
“…A 1g Raman peak observed from the exfoliated MoS 2 is blue-shifted from 403 to 401 cm −1 , while E 2g 1 Raman peak is red-shifted from 377 to 379 cm −1 . The results agree well with the literature that reported the E 2g 1 and A 1g modes are moving toward each other with decreasing layer thickness. 37 Moreover, the Raman peak difference of the exfoliated MoS 2 also approximate the number of MoS 2 layers, and a measured value of 22 cm −1 for the exfoliated MoS 2 dispersion corresponds to double-layer MoS 2 .…”
Section: Characterization Of Mossupporting
confidence: 92%
“…Research in gas sensors has attracted enormous interest due to the importance of industrial emission control, air quality monitoring, and building security . Specifically, volatile organic compounds (VOCs) are critical due to their role in tropospheric chemistry and their lethal effects on human health. , VOCs are gases emitted from either solid or liquid products such as paints, cleaners, and other office supplies such as copiers, adhesives, and furnishing coatings.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, solar energy, wind energy, and rain energy, all can be converted into electricity and promised to power sensor nodes in smart home applications. In Figure 4b, Song et al demonstrated a realistically available example for smart homes, titled as a wireless self-powered integrated nanostructured-gas-sensor network (SINGOR) for smart homes [174]. This SINGOR system consists of a power supply module, gas-sensing module, microcontroller-analog readout circuit, and wireless data transmission module, and Song et al had optimized each mode to obtain self-powered ability.…”
Section: Smart Homesmentioning
confidence: 99%
“…(b) Wireless self-powered high-performance integrated nanostructured-gas-sensor network (Reprinted with permission from ref. [174]. Copyright 2021 American Chemical Society).…”
Section: Smart Homesmentioning
confidence: 99%
See 1 more Smart Citation